KONFORMITAS PADA SOPIR AKBP TERHADAP PERILAKU KONTRAPRODUKTIF SUMATERA BARAT - Suci Anestra; Balqis Rahma Putri; Zakwan Adri (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2020)
This study aims to see the conformity of West Sumatra AKBP bus drivers in operating and to determine the effect of conformity on counterproductive work behavior. Researchers use indigenous methods with scientific questions in the form of google form. open and closed questions with 48 correspondents to explore that aspect. The results of research related to conformity of AKBP bus drivers with counterproductive behavior showed that only 8.69% of the data subjects engaged in counterproductive behavior while working, where the AKBP bus driver had the highest conformity with other colleagues when operating to exchange news about road conditions (32.60% ) which they will pass.